Annealing and surface conduction on Hydrogen peroxide treated bulk melt-grown, single crystal ZnO - Mtangi, W.; Nel, J.M.; Auret, F.D.; Chawanda, Albert; Diale, M.; Nyamhere, C. (Elsevier, 2016)
We report on the studies carried out on hydrogen peroxide treated melt-grown, bulk single crystal ZnO samples. Results show the existence of two shallow donors in the as-received ZnO samples with energy levels (37.8±0.3) meV that has been suggested as Zni related and possibly H-complex related and (54.5±0.9) meV, which has been assigned to an Al-related donor. Annealing studies performed on the hydrogen peroxide treated samples reveal the existence of a conductive channel in the samples in which new energy levels have been observed, Zn vacancies, related to the Group I elements, XZn. The surface donor volume concentration of the conductive channel was calculated from a theory developed by Look (2007) [1]. Results indicate an increase in the surface volume concentration with increasing annealing temperature from 60×1017 cm−3 at 200 °C to 4.37×1018 cm-3 at 800 °C.